Utilization of Hybrid Assembly Approach to Determine the Genome of an Opportunistic Pathogenic Fungus, Candida albicans TIMM 1768. (30th July 2018) - Panthee, Suresh; Hamamoto, Hiroshi; Ishijima, Sanae A; Paudel, Atmika; Sekimizu, Kazuhisa
Abstract: Candida albicans TIMM1768 is a highly virulent strain utilized as a model organism for the study of gastrointestinal and oral candidiasis. Despite being a model strain, identification of its genetic determinants of pathogenesis is hindered by the unavailability of its genome sequence. In this study, we determined the genome sequence of C. albicans TIMM1768 using reads obtained from portable MinION and benchtop Ion PGM sequencers. Genome annotation and a comparative analysis with published genomes revealed that the TIMM1768 strain was close to Candida albicans CHN1, and we identified a significant number of genes encoding for pathogenesis. The availability of the C. albicans TIMM1768 genome will facilitate comparative genomic analysis of Candida species, including studies of its virulence mechanisms and the development of treatment strategies for severe candidiasis.